Pemanfaatan Permainan Edukatif Digital untuk Meningkatkan Kemampuan Fonologis Anak Usia Dini - Santi Dwi Kartika; Sari Rahmi; Niko Ari Wibowo (Jurnal Pendidikan Bahasa dan Anak Usia Dini, 2025)
Phonological skills are a crucial foundation in early childhood language and literacy development. This study aims to explore the use of digital educational games as an interactive learning medium to improve young children's phonological abilities. A quasi-experimental method with a one-group pre-test and post-test design was applied. The participants were 4–5-year-old children enrolled in an early childhood education center in City X. Data were collected through observation sheets and phonological tests. The findings revealed a significant improvement in children's phonological skills after engaging with digital educational games regularly over a four-week period. The games were designed to train skills in sound discrimination, rhyme recognition, and syllable identification. These results imply that digital technology can serve as an innovative and effective tool to support phonological learning in an enjoyable manner during early childhood. The findings provide valuable insights for educators and application developers to design learning media appropriate to children's developmental stages.